Discontinuously Reinforced Titanium Matrix Composites Microstructure Design and Property Optimization - Huang, Lujun; Geng, Lin.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book introduces readers to titanium matrix composites (TMCs) with novel network microstructures. The bottleneck problem of extreme brittleness and low strengthening effect surrounding TMCs fabricated by means of powder metallurgy has recently been solved by designing network microstructures, which yield both high strength and superior ductility. As such, network structured TMCs will increasingly offer materials characterized by low weight, high strength, high temperature resistance and superior deformability. The book systematically addresses the design, fabrication, microstructure, properties, modification, and toughening mechanisms of these composites, which will help us find innovative solutions to a range of current and future engineering problems.
Introduction -- Design and fabrication of network structured pure Ti matrix composites -- Microstructure characteristics of Ti6Al4V matrix composites with network microstructure -- Mechanical behaviours of network structured TiBw/Ti64 composites -- Hot deformation behaviours of TiBw/Ti6Al4V composites with network microstructure -- Effects of heat treatment on microstructure and properties of TiBw/Ti6Al4V composites -- TiCp/Ti6Al4V and (TiCp+TiBw)/Ti6Al4V composites with network architecture -- Microstructure and properties of TiBw reinforced near-α Ti60 composites.
Keywords: Metals; Manufactures; Ceramic materials; Metals and Alloys; Machines, Tools, Processes; Ceramics